The use of a symbol in teaching subject : verb agreement - Mohamad Dahalan, Ardi Dasyni (2013)
Many students are found to be very weak in Subject-Verb-Agreement (SVA). They are always confused whether to put or not to put the letter ‘s’ at the end of the verb. Therefore this research is carried out to determine the effectiveness of teaching the grammar rules of Subject-Verb Agreement (SVA) using the ‘Snake’ pictures symbolising the letter ‘S’ for singular verbs in ‘Snake Attack’ activity. For the purpose of this study, 30 students of low to intermediate proficiency level from SMK Bandar Seri Alam were chosen as the respondents. One group was considered to be the experimental group who underwent the lesson using ‘Snake Attack’ activity and the other group as the control group underwent the traditional grammar lessons (prescriptive grammar). A pre-test and a number of treatments were conducted followed by a post-test to find out the effectiveness of the treatment and short interview sessions were held to find out students’ perception of the activity. Results showed that both groups showed improvement in their post-test results. However, the experimental group achieved a significant difference in their post-test results compared to the pre-test where all respondents attained same results or higher. Many of the students from the experimental group attained marks with differences of more than 50%. The results showed that the experimental group performed better than the control group. Subsequently, the interview sessions revealed that students preferred the ‘Snake Attack’ activity as it is fun and the rules are easy to comprehend and remember.